2020
DOI: 10.5435/jaaos-d-20-00339
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Utilization in Response to the Novel Coronavirus (COVID-19) Pandemic in Orthopaedic Surgery

Abstract: Introduction: The purpose of this investigation is to assess the current utilization of telehealth capabilities at academic orthopaedic departments in the United States and to determine how practice patterns have been directly influenced by the coronavirus disease 19 (COVID-19) pandemic. Methods: Orthopaedic surgery programs participating in the Electronic Residency Application Service were identified. One hundred seventy-five (175) programs were presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
162
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(179 citation statements)
references
References 9 publications
5
162
0
8
Order By: Relevance
“…In a recent study on the utilization of telehealth among orthopedic surgeons in response to COVID-19, Parisien et al demonstrated that 63.1% of Electronic Residency Application Service participating orthopedic institutions were currently providing telehealth accommodations whereas another 22.5% of programs were in the process of setting up telehealth services. 15 These findings are corroborated by our study, wherein we found a similar proportion offering telemedicine services. Geography has previously acted as both an incentive and barrier to the implementation of telehealth services.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a recent study on the utilization of telehealth among orthopedic surgeons in response to COVID-19, Parisien et al demonstrated that 63.1% of Electronic Residency Application Service participating orthopedic institutions were currently providing telehealth accommodations whereas another 22.5% of programs were in the process of setting up telehealth services. 15 These findings are corroborated by our study, wherein we found a similar proportion offering telemedicine services. Geography has previously acted as both an incentive and barrier to the implementation of telehealth services.…”
Section: Discussionsupporting
confidence: 86%
“…Geography has previously acted as both an incentive and barrier to the implementation of telehealth services. Although this study did not analyze responses on the basis of geography, Parisien et al 15 demonstrated that the majority of recently developed telehealth services in the orthopedic community have occurred in regions where COVID-19 has been more prevalent in the general population, with widespread implementation occurring in states such as California and New York. Our survey reached a wide-ranging audience, with all subspecialties represented, and a wide geographic spread.…”
Section: Discussionmentioning
confidence: 91%
“…There has been an exponential increase in the utilization of telehealth in orthopaedic surgery during the COVID-19 pandemic becuase this modality eliminates the risks associated with face-to-face interaction while still providing satisfactory and efficient patient care. 3 Although a fair amount of existing literature exploring the use of telehealth exists, the recent COVID-19 pandemic has exponentially increased the opportunity to explore this modality to provide safe and quality orthopaedic care.…”
Section: Discussionmentioning
confidence: 99%
“…Initially regarded as a modality to reach remote populations with limited access to medical services, its role has recently and rapidly expanded. 1 2 3 The widespread use of telemedicine has allowed for acceptable levels of uninterrupted medical care during periods of imposed isolation as is currently the situation resulting from the coronavirus (COVID-19) pandemic. During such a crisis, when the risks of close interpersonal contact may outweigh the benefits of a face-to-face visit, telemedicine offers a reasonable alternative.…”
mentioning
confidence: 99%
“…The emergence of such a crisis provides a timely opportunity for us to re ect and evaluate the use of novel technologies in the workplace. This includes the adoption of telemedicine and telerehabilitation initiatives, allowing patients to be consulted and followed-up in the comfort of their own homes [4,5,[8][9][10].…”
Section: Discussionmentioning
confidence: 99%